Movement Analysis of DIMAS SAPUTRA Smash with Kinovea in the West Kalimantan Regional KAPOLDA CUP I Volleyball Final - Suhairi, Muhammad; Rahmat, Ade; Rajidin; Syaparudin; Rusmita, Yuyun (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. Biomechanics is a branch of science that studies the forms and types of human movement based on mechanical principles in a sport that can minimize the occurrence of sports injuries. The purpose of this study was to see the effectiveness of Dimas Saputra's smash open movement at the 2023 West Kalimantan Regional Police Chief Championship. Materials and methods. The esearch technique in this study used observation techniques through documentation. The documentation is done by taking a video of Dimas Saputra's volleyball game and observing the video. In carrying out this research using biomechanical analysis related to Dimas Saputra's smash motion open technique by inserting the video into the Kinovea application and analyzing it. Results. The results showed that in volleyball games, of course, a spiker is greatly helped by a height above 185 cm. With this height, a person will find it easier and more effective when making jumping movements. Second, the right timing when doing the spike is also an important point for a volleyball athlete, good timing will also be influenced by the speed when doing the jump and arm swing before the topspin phase occurs. Conclusion. Based on research that has been carried out on the analysis of Dimas Saputra's smash movements in the Final Four of the 2023 West Kalimantan Regional Police Chief Championship, it can be seen that an ideal volleyball player must have a height above 185 cm for the spiker position, besides that volleyball players must also have good timing right in taking a bait. It can be trained by doing smash drills and ball coordination exercises. Finally, a volleyball player ideally must also have strong and fast arm swing strength supported by good core muscle strength.